As grades que envolvem o berço : maternidades no contexto do Presídio Estadual Feminino Madre Pelletier - Oliveira, Luiza Dias de (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation addresses the context of motherhood within the prison system, from the Maternal and Child Unit, at the Madre Pelletier Female State Prison, in Porto Alegre, Rio Grande do Sul, in the period of July of 2018. In this context, I try to understand how the experience of motherhood happens, permeated by the State and crossed by the relations between inmate and staff, inmate and inmate and with their families. The analysis was developed from the perspective of State Anthropology. The preferred methodology of this research was ethnography, based on participant observation, interviews and field diary. Field research was fundamental in building an understanding of the pathways of the state, the imbrications of motherhood in the prison environment and the intersectionalities of gender and race that cross the system. It was possible to verify the ways in which the State is present and absent in the lives of these incarcerated women, from the judicial processes to the relations with the staff and agents, sometimes affective and by others full of tensions. It was also possible to verify the selectivity of the system, by analyzing the data provided by the inmates themselves, as well as perceived forms of racism in the system. Complementarily, the relations between mothers and babies were widely observed, and it is possible to conclude that women are subjected to direct and continuous confinement with their children, in order to be separated from them later.
Keywords: Maternidade; Prisão; Estado; Interseccionalidades; Presídio Estadual Feminino Madre Pelletier; Maternity; Prison; State; Intersectionality; Madre Pelletier Female State Prison; ACCNPQ::Ciências Humanas::Sociologia